The Effect of Heat& Cold on The L.monocytogenes in the Milk - Al-Khatib, Ghazi M.; J.Alwan , Mohammed; M. Al-Jebouri, Nagham (The Iraqi Journal of Veterinary Medicine, 2007)
The influence of heat and cold on the L.monocytogenes in the milkIn order to know the thermal resistance of L.monocytogenesin thecontaminated milk, 40gram of powder milk was dissolved in 400mlof heated water.The milk solution was sealed in 40 test tubes 10 mlin each one.these test tubes were divided into 6 groups ,10test tubesin each the 1st,2nd group &5 test tubes in each the 3rd ,4th ,5th ,6thgroups,then all the test tubes were inoculated withL.monocytogenes &incubation for 24hrs at 37c.the samples of the1st &2nd group were dipped in awater bath at tempreture 63c for30minute &72c for 1-5.5 minute respectively .also the samples of3rd &4th groups were dipped in awater bath at 72c for 6minute. Testtubes of 1st ,3rd ,5th groups were kept in 4c for variable times whilesamples of 4th ,6th group were exposured to - 18c for 12days. Theresults showed no bacterial isolates immediately after heattreatment in all the milk samples of 1st .3rd &4th groups but someisolates were seen after enrichment at 4c&- 18c L.monocytogeneswas isolate from all samples of 2nd ,5th &6th groups. The resultssuugest that cold enrichment play role in repair the thermallyinjured cells of L.monocytogenes&these organisms survivevethermal treatment.